Could mindfulness-based cognitive therapy prevent a lifelong recurrent course of depression or anxiety by addressing key mechanisms of vulnerability in high-risk adolescents?. (April 2020) - Ford, Tamsin; Richardson, Jessica; Wilkinson, Kath; Smith, Patrick; Berry, Vashti; Barnhofer, Thorsten; Fox, Jerry; Kuyken, Willem
Summary: We explore the potential of mindfulness-based cognitive therapy, a skills-based intervention that provides participants with sustainable tools for adaptive responses to stress and negative mood, for the large group of young people with depression or anxiety who only partially or briefly respond to currently available first-line interventions.